2018
DOI: 10.14814/phy2.13919
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced reduction of adipose eosinophils is reversed with low-calorie dietary intervention

Abstract: While many studies have characterized the inflammatory disposition of adipose tissue (AT) during obesity, far fewer have dissected how such inflammation resolves during the process of physiological weight loss. In addition, new immune cells, such as the eosinophil, have been discovered as part of the AT immune cell repertoire. We have therefore characterized how AT eosinophils, associated eosinophilic inflammation, and remodeling processes, fluctuate during a dietary intervention in obese mice. Similar to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…In accordance with previous studies, we also observed a decrease in the adipose eosinophils in response to a WSD ( Figure 1H). [17][18][19] Finally, in contrast to some studies, we did not observe an increase in adipose neutrophils in response to WSD feeding ( Figure 1H). [20][21][22] We recently reported that a WSD induces dramatic morphologic changes in the colon.…”
Section: Characterization Of Changes In Tissue Leukocytes In Responsecontrasting
confidence: 99%
“…In accordance with previous studies, we also observed a decrease in the adipose eosinophils in response to a WSD ( Figure 1H). [17][18][19] Finally, in contrast to some studies, we did not observe an increase in adipose neutrophils in response to WSD feeding ( Figure 1H). [20][21][22] We recently reported that a WSD induces dramatic morphologic changes in the colon.…”
Section: Characterization Of Changes In Tissue Leukocytes In Responsecontrasting
confidence: 99%
“…The effects of caloric restriction on bone health is still poorly understood. Generally, caloric restriction, accompanied with weight loss, has a positive effect on systemic glucose tolerance and inflammatory status of immune cells and their count (neutrophils) (169,174). A recent study by Collins et al (160) showed that dietary caloric restriction protects BM and optimizes immunological responses of immune cells by enhanced accumulation of memory T lymphocytes in BM, erythropoiesis and bone marrow adiposity.…”
Section: Life-style Interventions: Dietary and Physical Activity Intementioning
confidence: 99%
“…Notably, Bolus et al. showed that the decrease in adipose tissue eosinophils with obesity can be reversed after dietary intervention and weight loss 30 …”
Section: The Systemic and Local Effects Of Adipose Eosinophils In Obementioning
confidence: 99%